IMPLEMENTATION OF NEW DIGITAL TECHNOLOGIES IN SPORTS EDUCATIONAL PROCESS - Ryskin, Petr; V. Davydova, Elena; Fagina, Stanislava; Shuraleva, Natalia N (Revista Inclusiones, 2020)
The relevance of the study is due to the need to determine ways to adapt digital technologies to the specifics of training in the field of physical culture and sports. The aim of the study is to determine the features of the use of digital technologies in sports events. The study was conducted at the Department of Physical Education and Sports of the Ural State University of Economic in the period 2017-2019, during mass sporting events. The information base of the study consists of observation materials for149 participants of the “Nations Cross». The research methodology is based on the use of geo-information systems to track the route of the race participants. The data obtained show that when adjusting the results of the race according to the parameters ofthe geolocation, some of the participants shortened the route because of which they received overrated indicators.